2017
DOI: 10.3892/or.2017.5850
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and chemosensitization effects of Scutellarin from traditional Chinese herb Scutellaria altissima L. in human prostate cancer cells

Abstract: Scutellaria altissima L. is a common traditional Chinese medicine used to treat inflammation in some countries. Scutellarin, an active major flavone glycoside isolated from the traditional Chinese medicine Scutellaria altissima L., has been shown to offer various beneficial biochemical effects on cerebrovascular diseases and inflammation. However, the antiproliferative effects of Scutellarin in prostate cancer and the underlying mechanism are not fully elucidated. In the present study, we aimed to ascertain wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 35 publications
(34 reference statements)
0
29
0
Order By: Relevance
“…reported that SCU effectively inhibits hepatocellular carcinoma metastasis in vivo and the migration and invasion of hepatocellular carcinoma cells in vitro . Other researchers have reported that SCU induces apoptosis and G2/M arrest, inhibits cell proliferation of prostate cancer PC3 cells, and sensitizes the cells to chemotherapy …”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…reported that SCU effectively inhibits hepatocellular carcinoma metastasis in vivo and the migration and invasion of hepatocellular carcinoma cells in vitro . Other researchers have reported that SCU induces apoptosis and G2/M arrest, inhibits cell proliferation of prostate cancer PC3 cells, and sensitizes the cells to chemotherapy …”
Section: Discussionmentioning
confidence: 98%
“…21 Other researchers have reported that SCU induces apoptosis and G2/M arrest, inhibits cell proliferation of prostate cancer PC3 cells, and sensitizes the cells to chemotherapy. 16 In this study, we first investigated the toxicity of SCU to A549 lung adenocarcinoma cells. Using CCK-8 and colony formation assays, our results show that SCU effectively suppresses the proliferation of A549 cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prominent constituents of this family include flavonoids, phenolic acids, lipophilic tanshinones , sesquiterpenoids, diterpenoids, and triterpenoids. Nepeta cataria, Scutellaria altissima, Salvia miltiorrhiza, Salvia chorassanica, and Salvia miltiorrhiza, all members of the Lamiaceae family exhibited cytotoxic effects on DU145, PC-3, or LNCaP prostate cancer cells and induced cell cycle arrest and subsequent apoptosis via a variety of mechanisms [28,[41][42][43][44]. PC-3 cells treated with extract from Scutellaria altissima, which contains predominantly scutellarin, a flavone glycoside, arrest in the GAP2/mitotic phase as a result of the increased expression of cyclin B1 and Cdc2 [43].…”
Section: Effects Of Extracts From Specific Plant Families On Human Prmentioning
confidence: 99%